Admissibility of a cassation appeal against the judgment on discontinuance of proceedings due to a perpetrator’s insanity and application of preventive measures (Ius Novum, 2020)
The article aims to present interpretative doubts that are raised in connection with admissibility of a cassation appeal against a judgment concerning the discontinuance of proceedings and application of preventive measures, as well as to assess the latest legislative changes that result in the extension of the objective scope of cassation by judgments issued on this matter.
Keywords: criminal proceedings; cassation appeal against a ruling on the discontinuance of proceedings and application of a preventive measure; extension of the objective scope of cassation; admissibility of a cassation appeal against a ruling